A high-efficiency and stable micro-etching treatment liquid for micro-etching and a preparation method thereof
By using components such as sulfuric acid and persulfate in the micro-etching treatment solution, the problems of instability and low efficiency of the existing micro-etching system in copper surface treatment are solved, efficient and uniform copper surface micro-etching and long-term prevention of oxidation are achieved, and the quality and service life of the circuit board are improved.
Patent Information
- Application Number
- CN202411108802.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-08-13
AI Technical Summary
During the use of the existing micro-etching system, the roughness and uniformity of the copper surface are difficult to control, which can easily lead to short circuit failure of the circuit board, low processing capacity, serious waste of resources, low stability and efficiency, affecting the normal use of the circuit board.
Provided is a highly efficient and stable micro-etching treatment liquid containing sulfuric acid, persulfate, copper ions, tartaric acid, polyethylene glycol, corrosion inhibitor, stabilizer, surfactant and accelerator. Through the synergistic action of these components, efficient etching, protection of copper surface, preventing oxidation and enhancing adhesion.
The uniform micro-etching of the copper surface is achieved, keeping the surface bright and clean, preventing oxidation for a long time, reducing the etching amount, enhancing the adhesion between the copper/dielectric material layers, and improving the stability and service life of the micro-etching treatment liquid.
Smart Images

Figure BDA0004991570550000081 
Figure BDA0004991570550000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of printed circuit board production, and in particular to a highly efficient and stable micro-etching treatment liquid for micro-etching treatment and a preparation method thereof. Background Art
[0002] Printed Circuit Board (FPC) is an electronic component that supports electronic components and provides electrical connections. It is light, consistent, small, reliable, and easy to standardize. It has been widely used in digital products, aerospace, smart home appliances, communications, medical and other high-tech electronic products. As a basic component of electronic products, the performance of printed circuit boards plays a vital role in the service life of electronic products. In recent years, with the development of electronic products towards multifunctionality, miniaturization, high density, and high efficiency, higher requirements have been put forward for the refinement of the preparation and application reliability of printed circuit boards.
[0003] At present, printed circuit boards are usually made of copper-clad laminates as the substrate and processed through multiple processes. Among them, micro-etching and cleaning treatment is an important processing step in the preparation of printed circuit boards and is the key to achieving refined circuit board preparation and improving the quality of refined circuit boards. The use of micro-etching agents to micro-etch the copper surface can form a microscopic rough structure on the surface of the copper layer and enhance the adhesion between the bonding layer and the copper layer.
[0004] In order to achieve the ideal micro-etching effect, the performance requirements for the micro-etching agent are relatively high. At present, the composite system of sulfuric acid + hydrogen peroxide + surfactant is still the mainstream micro-etching system due to its high micro-etching efficiency and convenient waste liquid recovery. However, although the conventional micro-etching system can achieve a certain micro-etching effect, various problems are gradually exposed during actual use. For example, the roughness and uniformity of the copper surface are difficult to effectively control, which easily leads to short-circuit failures on the circuit board; the system's processing capacity is low, and the tank liquid needs to be replaced frequently after reaching the copper ion holding capacity, resulting in a waste of resources; in addition, the existing micro-etching system also has insufficient polishing and protection, which easily causes oxidation or discoloration of the copper surface, as well as poor stability and low efficiency of the micro-etching system, which greatly affects the normal use of the circuit board. Summary of the invention
[0005] The purpose of the present application is to provide a high-efficiency and stable micro-etching treatment liquid for micro-etching treatment and a preparation method thereof in view of the deficiencies in the current technology. The high-efficiency and stable micro-etching treatment liquid for micro-etching treatment of the present application has excellent stability while having a high etching rate. The micro-etching of the copper surface obtained by the treatment of the present application is uniform, bright and clean, and can effectively prevent the oxidation of the copper surface for a long time, which is beneficial to reduce the etching amount and enhance the adhesion between the copper / dielectric material layers. The roughness of the copper surface after micro-etching is uniform, and it is suitable for micro-etching treatment of circuit boards.
[0006] In the first aspect, the present application provides an efficient and stable micro-etching treatment solution for micro-etching, which adopts the following technical solution:
[0007] A highly efficient and stable micro-etching treatment solution for micro-etching treatment, comprising the following raw materials by mass concentration: 98% sulfuric acid 2.8-3.2g / L, persulfate 90-120g / L, copper ion Cu 2+ ≤24g / L, tartaric acid 3-5g / L, polyethylene glycol 10-12g / L, corrosion inhibitor 3-6g / L, stabilizer 3-5g / L, surfactant 1-2g / L, accelerator 4-6g / L, wherein the copper ion Cu 2+ Supplied by a copper ion source.
[0008] By adopting the above technical solution, sulfuric acid: As part of the etchant, sulfuric acid helps to increase the etching rate, but its concentration needs to be controlled to balance efficiency and copper surface protection. Persulfate: One of the main etching components, responsible for the dissolution process of copper, its concentration has a direct impact on the etching rate. Copper ion Cu 2+ : Provided by the copper ion source, it participates in the etching process, but its concentration needs to be controlled within a specific range to avoid over-etching. Tartaric acid: Combined with polyethylene glycol, it can inhibit further oxidation of the copper surface after micro-etching, keeping the copper surface bright and clean. Polyethylene glycol: Forms a protective film on the copper surface, and works together with tartaric acid to improve the antioxidant properties of the copper surface after micro-etching. Corrosion inhibitor: By forming a protective film, it slows down the etching of the copper surface by the etchant, reduces the loss of the copper surface, and enhances the film-forming property to prevent H + Ions react with copper too quickly. Stabilizer: Improves the stability of the micro-etching system, extends the service life of the bath, and increases the capacity for copper ions through adsorption to solve the problem of low copper dissolution. Surfactant: Improves the stability and wettability of the liquid to ensure the uniformity of the etching process. Accelerator: Promotes the coarsening of the copper surface to form a uniform and dense microscopic pore structure, which is beneficial to enhance the adhesion between the copper / dielectric material layers. The design of this micro-etching treatment liquid takes into account multiple aspects of copper surface treatment, including etching efficiency, copper surface protection, and the quality of the copper surface after treatment. Through the synergistic effect of these components, it is intended to achieve an efficient etching process while maintaining the quality of the copper surface, reducing losses, and improving the overall treatment effect.
[0009] Preferably, the stabilizer is composed of ethylenediaminetetraacetic acid, diethylene glycol methyl ethyl ether and modified polyacrylonitrile in a mass ratio of 5:2:2-3.
[0010] By adopting the above technical solution, ethylenediaminetetraacetic acid (EDTA) in the micro-etching treatment solution helps to control the activity of copper ions and prevent copper from dissolving too quickly, thereby maintaining copper ions within a suitable concentration range and ensuring the uniformity and controllability of the etching process. In addition, EDTA can also reduce the impact of metal ions on other components and improve the overall stability of the solution. Diethylene glycol methyl ethyl ether (DEGME): This compound is usually used as a solvent and coupling agent. It may play a role in regulating the compatibility of various components in the micro-etching treatment solution to ensure the stability and uniformity of the solution. At the same time, it may also help improve the wettability of the treatment solution on the copper surface, thereby improving the uniformity of the etching effect. Modified polyacrylonitrile (MPAN): As a polymer material, modified polyacrylonitrile may play the role of stabilizer and dispersant in the solution. It can help stabilize the particles in the solution and prevent precipitation. At the same time, it may have a certain protective effect on the copper surface and reduce the unevenness during the etching process. EDTA reduces the number of free copper ions by chelating copper ions, reduces the potential impact of copper ions on other components, and also slows down the etching rate of copper, making the etching process more controllable. DEGME, as a coupling agent and solvent, improves the compatibility between the components and improves the wettability of the treatment solution on the copper surface, which is conducive to forming a uniform etching effect. MPAN, as a stabilizer and dispersant, helps maintain the stability of the solution, prevents the separation or precipitation of components, and ensures that long-term use will not reduce the etching effect. In summary, these three stabilizers, through their respective characteristics and interactions, jointly maintain the stability of the micro-etching treatment solution and the uniformity of the etching effect, and are one of the key factors in achieving efficient and stable micro-etching treatment.
[0011] Preferably, the preparation method of the modified polyacrylonitrile is: 10 parts of polyacrylonitrile powder are subjected to low-temperature heat treatment at 240°C for 2 hours in an air atmosphere, then cooled to room temperature, and then immersed in 50 parts of a 20wt% diethylenetriamine aqueous solution for 2-3 hours, and then washed with deionized water after immersion, and then dried at 90°C for 6-8 hours to obtain modified polyacrylonitrile.
[0012] By adopting the above technical scheme, modified polyacrylonitrile (MPAN) is prepared through a specific chemical and thermal treatment process, which includes low-temperature heat treatment of polyacrylonitrile powder in an air atmosphere, followed by immersion treatment in a diethylenetriamine aqueous solution, and finally washing and drying. This modification process is intended to introduce new functional groups and change its physical and chemical properties to make it more suitable as a stabilizer in a micro-etching treatment solution. Modified polyacrylonitrile can be used as a stabilizer to help maintain the stability of other chemical components in the micro-etching treatment solution, reduce the possibility of component separation or precipitation, and ensure that long-term use will not reduce the etching effect. Modified polyacrylonitrile may have the ability to adsorb copper ions, which helps to adjust the concentration of copper ions in the micro-etching treatment solution, extend the service life of the bath solution, and solve the problem of low copper dissolution. As a polymer material, modified polyacrylonitrile may also improve the wettability of the treatment solution on the copper surface, which is conducive to forming a uniform etching effect. Combined with ethylenediaminetetraacetic acid and diethylene glycol methyl ethyl ether, modified polyacrylonitrile can improve the micro-etching system's capacity to accommodate copper ions, reduce the decomposition rate of persulfate, improve the stability of copper coating dissolution efficiency, and achieve micro-etching speed control. In general, the use of modified polyacrylonitrile in micro-etching treatment liquid not only provides effective control of copper ions and a stable etching environment, but also improves the efficiency and quality of the entire micro-etching process through its unique chemical properties and physical state, working together with other components.
[0013] Preferably, the corrosion inhibitor is composed of 1-butyl-3-methylimidazolium tetrafluoroborate, dibenzotriazole and modified imidazoline corrosion inhibitor in a mass ratio of 3:2:5.
[0014] By adopting the above technical solutions, 1-butyl-3-methylimidazolium tetrafluoroborate: This compound is usually used as part of ionic liquids and has good thermal and chemical stability. In the micro-etching treatment solution, it may play the role of providing stable charge carriers, which helps to uniformly etch the copper surface. Dibenzotriazole: This is a commonly used metal corrosion inhibitor, especially effective for copper and copper alloys. It can form a dense protective film to prevent the corrosive medium from directly contacting the metal surface, thereby slowing down the corrosion process. Modified imidazoline corrosion inhibitor: As you mentioned, this corrosion inhibitor enhances film formation through its long-chain alkyl and oligomer structure. The hydrophobic film formed can effectively prevent H+ ions from reacting with copper and protect the copper surface from being etched too quickly. 1-Butyl-3-methylimidazolium tetrafluoroborate provides stable charge carriers and helps to uniformly etch; dibenzotriazole and modified imidazoline corrosion inhibitors protect the copper surface by forming a physical barrier layer to reduce direct corrosion. The different action mechanisms of the three corrosion inhibitors complement each other and may form a multi-layer protective structure on the copper surface, thereby providing more comprehensive and lasting protection. This composite corrosion inhibition system not only improves the protective effect of the copper surface, but also improves the surface quality after micro-etching, making the copper surface brighter and cleaner, and reducing the need for subsequent treatment. In summary, this composite corrosion inhibition system composed of 1-butyl-3-methylimidazolium tetrafluoroborate, dibenzotriazole and modified imidazoline corrosion inhibitor, through their respective specific effects and synergistic effects, jointly improves the performance of the micro-etching treatment solution, ensures efficient and uniform etching of the copper surface, and effectively prevents oxidation and corrosion of the copper surface.
[0015] Preferably, the preparation method of the modified imidazoline corrosion inhibitor is as follows: according to the mass fractions, 170 parts of erucic acid and 100 parts of tetraethylenepentamine are put into a reactor, the temperature is raised to 150° C. and stirred for reaction for 3-4 hours, and the temperature is further raised to 210° C. and stirred for reaction for 3-4 hours to obtain the modified imidazoline corrosion inhibitor.
[0016] By adopting the above technical scheme, the preparation method of the modified imidazoline corrosion inhibitor involves reacting erucic acid and tetraethylenepentamine under specific conditions to form an oligomer structure with long-chain alkyl and ethyleneimine groups. The role of this structure in the micro-etching treatment solution is mainly reflected in the following aspects: the long-chain alkyl and oligomer structure in the modified imidazoline corrosion inhibitor enhance its ability to form a protective film on the copper surface. This protective film can effectively prevent H +The ions react too quickly with copper, thereby slowing down the etching rate of copper and protecting the copper surface from excessive etching. The nitrogen atoms on the heterocyclic ring can provide electrons to form coordination bonds with copper. This chemical bonding helps the corrosion inhibitor molecules to be evenly distributed on the copper surface, forming a uniform protective layer, further improving the protective effect of the copper surface. The hydrophobic film formed by the modified imidazoline corrosion inhibitor can effectively block the contact between moisture and corrosive substances and the copper surface, reduce copper oxidation and other forms of corrosion, and keep the copper surface bright and clean. In combination with other components such as tartaric acid and polyethylene glycol, the modified imidazoline corrosion inhibitor can work together to further inhibit the oxidation of the copper surface and improve the stability and corrosion resistance of the copper surface after micro-etching. In short, the modified imidazoline corrosion inhibitor plays a key protective role in the micro-etching treatment solution through its unique chemical structure and reaction characteristics, which not only improves the micro-etching efficiency, but also ensures the quality of the copper surface after treatment, showing its application potential in the field of metal surface treatment.
[0017] Preferably, the surfactant is composed of isomeric tridecanol polyoxyethylene ether and sodium cumene sulfonate in a mass ratio of 3:2.
[0018] By adopting the above technical scheme, surfactants play a vital role in the micro-etching treatment liquid. They reduce the surface tension of the liquid, improve the wettability of the copper surface, and ensure that other chemical components can contact the copper surface more evenly and effectively. The surfactant is composed of isomeric tridecanol polyoxyethylene ether and sodium cumene sulfonate in a mass ratio of 3:2. These two compounds each have unique properties, and there is a synergistic effect between them, thereby enhancing the overall performance of the micro-etching treatment liquid. Isomeric tridecanol polyoxyethylene ether: This non-ionic surfactant has good wetting and penetration ability, which can help the treatment liquid better cover the copper surface, thereby improving the uniformity of etching. Its molecular structure enables it to form a thin adsorption layer on the metal surface, which helps to stabilize the state of the copper surface and reduce the unevenness that may occur during the etching process. Sodium cumene sulfonate: As an anionic surfactant, it can provide good cleaning and emulsifying properties. During the micro-etching process, it helps to remove grease and other organic pollutants on the copper surface, ensure that the chemical etchant can directly act on the copper surface, and improve the etching efficiency. The combination of isomeric tridecanol polyoxyethylene ether and sodium cumene sulfonate can combine the advantages of both to achieve better wetting, cleaning and stability. The mixed use of non-ionic surfactants and anionic surfactants can improve the solution's cleaning ability for different types of contaminants while maintaining good wettability on the copper surface, which is critical for achieving a uniform and effective etching process. In addition, this combination can also reduce the amount of surfactant used in the solution, thereby reducing costs and reducing environmental impact.
[0019] Preferably, the accelerator is 2-mercapto-1-methylimidazole.
[0020] Preferably, the persulfate is one of potassium hydrogen persulfate, sodium persulfate and potassium persulfate.
[0021] Preferably, the copper ion source is one of copper chloride and copper sulfate.
[0022] In a second aspect, the present application provides a method for preparing an efficient and stable micro-etching treatment liquid for micro-etching treatment, which adopts the following technical solution:
[0023] As a general technical concept, the present application also provides a method for preparing the above-mentioned efficient and stable micro-etching treatment solution for micro-etching treatment, comprising the following steps:
[0024] 2.8-3.2g of 98% sulfuric acid, 90-120g of persulfate, and copper ion Cu 2+ ≤24g, tartaric acid 3-5g, polyethylene glycol 10-12g, corrosion inhibitor 3-6g, stabilizer 3-5g, surfactant 1-2g, and accelerator 4-6g are added to an appropriate amount of deionized water and mixed evenly, and then the mixed solution is fixed to 1L to obtain an efficient and stable micro-etching treatment solution for micro-etching treatment.
[0025] In summary, the beneficial technical effects of this application are:
[0026] 1. Improve etching efficiency: By precisely controlling the concentration of each component, especially sulfuric acid and persulfate, an efficient etching rate is ensured. The proper addition of copper ions also helps maintain a stable etching process.
[0027] 2. Protect the copper surface: The application of modified imidazoline corrosion inhibitor forms a protective film on the copper surface through its unique chemical structure, which effectively slows down the reaction rate between H+ ions and copper, thereby protecting the copper surface from excessive etching and keeping the copper surface bright and clean.
[0028] 3. Anti-oxidation: The combination of tartaric acid and polyethylene glycol not only inhibits further oxidation of the copper surface after micro-etching, but also forms an additional protective layer on the copper surface, effectively preventing oxidation and discoloration problems caused by long-term exposure to air.
[0029] 4. Enhanced adhesion: The addition of accelerators causes the copper surface to form a uniform and dense microscopic pore structure, which is conducive to enhancing the adhesion between copper and the dielectric material in subsequent applications.
[0030] 5. Improve stability: By introducing ethylenediaminetetraacetic acid, diethylene glycol methyl ethyl ether and modified polyacrylonitrile as composite stabilizers, not only the decomposition rate of persulfate is reduced and the overall stability of the micro-etching system is improved, but also the system's capacity for copper ions is increased by adsorbing copper ions, thereby extending the service life of the bath.
[0031] 6. Improved wettability: The addition of surfactants improves the stability and wettability of the liquid, ensuring the uniformity of the etching process, thereby improving the processing efficiency and the quality of the copper surface. DETAILED DESCRIPTION
[0032] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0033] Preparation Example 1 Preparation of modified polyacrylonitrile
[0034] The preparation method of modified polyacrylonitrile is as follows: 100g of polyacrylonitrile powder is subjected to low-temperature heat treatment at 240°C for 2h in an air atmosphere, then cooled to room temperature, and then immersed in 500g of a 20wt% diethylenetriamine aqueous solution for 2.5h. After immersion, it is cleaned with deionized water and then dried at 90°C for 7h to obtain modified polyacrylonitrile.
[0035] Preparation Example 2 Preparation of modified imidazoline corrosion inhibitor
[0036] The preparation method of the modified imidazoline corrosion inhibitor is as follows: according to the mass fractions, 170g of erucic acid and 100g of tetraethylenepentamine are put into a reactor, the temperature is raised to 150°C and stirred for reaction for 3.5h, the temperature is further raised to 210°C and stirred for reaction for 3.5h to obtain the modified imidazoline corrosion inhibitor.
[0037] Example 1
[0038] A highly efficient and stable micro-etching treatment solution for micro-etching treatment, comprising the following raw materials by mass concentration: 2.8 g / L sulfuric acid with a mass concentration of 98%, 90 g / L potassium persulfate, and copper ions Cu 2+ 24g / L, tartaric acid 3g / L, polyethylene glycol 10g / L, corrosion inhibitor 3g / L, stabilizer 3g / L, surfactant 1g / L, 2-mercapto-1-methylimidazole 4g / L, wherein the copper ion Cu 2+ It is provided by cupric chloride, the stabilizer is composed of ethylenediaminetetraacetic acid, diethylene glycol methyl ethyl ether and modified polyacrylonitrile in a mass ratio of 5:2:2, the corrosion inhibitor is composed of 1-butyl-3-methylimidazole tetrafluoroborate, dibenzotriazole and modified imidazoline corrosion inhibitor in a mass ratio of 3:2:5, and the surfactant is composed of isomeric tridecanol polyoxyethylene ether and sodium isopropylbenzene sulfonate in a mass ratio of 3:2.
[0039] The above-mentioned method for preparing a highly efficient and stable micro-etching treatment liquid for micro-etching treatment comprises the following steps:
[0040] 2.8 g of 98% sulfuric acid, 90 g of potassium persulfate, and copper ion Cu 2+ 24g, tartaric acid 3g, polyethylene glycol 10g, corrosion inhibitor 3g, stabilizer 3g, surfactant 1g, 2-mercapto-1-methylimidazole 4g are added to an appropriate amount of deionized water and mixed evenly, and then the mixed solution is fixed to 1L to obtain an efficient and stable micro-etching treatment solution for micro-etching treatment.
[0041] Example 2
[0042] A highly efficient and stable micro-etching treatment solution for micro-etching treatment, comprising the following raw materials by mass concentration: 3.2 g / L sulfuric acid with a mass concentration of 98%, 120 g / L sodium persulfate, and copper ions Cu 2+ 20g / L, tartaric acid 5g / L, polyethylene glycol 12g / L, corrosion inhibitor 6g / L, stabilizer 5g / L, surfactant 2g / L, 2-mercapto-1-methylimidazole 6g / L, wherein the copper ion Cu 2+ It is provided by copper sulfate, the stabilizer is composed of ethylenediaminetetraacetic acid, diethylene glycol methyl ethyl ether and modified polyacrylonitrile in a mass ratio of 5:2:3, the corrosion inhibitor is composed of 1-butyl-3-methylimidazole tetrafluoroborate, dibenzotriazole and modified imidazoline corrosion inhibitor in a mass ratio of 3:2:5, and the surfactant is composed of isomeric tridecyl alcohol polyoxyethylene ether and sodium isopropylbenzene sulfonate in a mass ratio of 3:2.
[0043] The above-mentioned method for preparing a highly efficient and stable micro-etching treatment liquid for micro-etching treatment comprises the following steps:
[0044] 3.2 g of 98% sulfuric acid, 120 g of sodium persulfate, and copper ion Cu 2+ 20g, tartaric acid 5g, polyethylene glycol 12g, corrosion inhibitor 6g, stabilizer 5g, surfactant 2g, 2-mercapto-1-methylimidazole 6g are added to an appropriate amount of deionized water and mixed evenly, and then the mixed solution is diluted to 1L to obtain an efficient and stable micro-etching treatment solution for micro-etching treatment.
[0045] Example 3
[0046] A highly efficient and stable micro-etching treatment solution for micro-etching treatment, comprising the following raw materials by mass concentration: 3 g / L sulfuric acid with a mass concentration of 98%, 100 g / L potassium persulfate, and copper ions Cu 2+ 15g / L, tartaric acid 4g / L, polyethylene glycol 11g / L, corrosion inhibitor 4g / L, stabilizer 4g / L, surfactant 1.5g / L, 2-mercapto-1-methylimidazole 5g / L, wherein the copper ion Cu2+ It is provided by copper sulfate, the stabilizer is composed of ethylenediaminetetraacetic acid, diethylene glycol methyl ethyl ether and modified polyacrylonitrile in a mass ratio of 5:2:2.5, the corrosion inhibitor is composed of 1-butyl-3-methylimidazole tetrafluoroborate, dibenzotriazole and modified imidazoline corrosion inhibitor in a mass ratio of 3:2:5, and the surfactant is composed of isomeric tridecyl alcohol polyoxyethylene ether and sodium isopropylbenzene sulfonate in a mass ratio of 3:2.
[0047] The above-mentioned method for preparing a highly efficient and stable micro-etching treatment liquid for micro-etching treatment comprises the following steps:
[0048] 3g of 98% sulfuric acid, 100g of potassium persulfate, and copper ion Cu 2+ 15g, 4g of tartaric acid, 11g of polyethylene glycol, 4g of corrosion inhibitor, 4g of stabilizer, 1.5g of surfactant, and 5g of 2-mercapto-1-methylimidazole are added to an appropriate amount of deionized water and mixed evenly, and then the mixed solution is diluted to 1L to obtain an efficient and stable micro-etching treatment solution for micro-etching treatment.
[0049] Comparative Example 1
[0050] The same as Example 3, except that the stabilizer is ethylenediaminetetraacetic acid.
[0051] Comparative Example 2
[0052] The same as Example 3, except that the stabilizer is diethylene glycol methyl ethyl ether.
[0053] Comparative Example 3
[0054] The same as Example 3, except that the stabilizer is modified polyacrylonitrile.
[0055] Comparative Example 4
[0056] The same as Example 3, except that the corrosion inhibitor is 1-butyl-3-methylimidazolium tetrafluoroborate.
[0057] Comparative Example 5
[0058] The same as Example 3, except that the corrosion inhibitor is dibenzotriazole.
[0059] Comparative Example 6
[0060] The same as Example 3, except that the corrosion inhibitor is a modified imidazoline corrosion inhibitor.
[0061] Comparative Example 7
[0062] The same as Example 3, except that the surfactant is isomeric tridecanol polyoxyethylene ether.
[0063] Comparative Example 8
[0064] The same as Example 3, except that the surfactant is sodium cumene sulfonate.
[0065] Performance Testing
[0066] The high-efficiency and stable micro-etching treatment solutions for micro-etching prepared in Examples 1 to 3 and Comparative Examples 1 to 8 were subjected to the following performance tests. The test results are shown in Table 1.
[0067] 1. Determination of micro-etching rate: The high-efficiency and stable micro-etching treatment solutions provided in Examples 1 to 3 and Comparative Examples 1 to 8 were respectively added to the spray machine, and then 11 copper-clad substrates (10 cm×10 cm) were taken respectively. The copper-clad substrates were pickled with an aqueous solution of sulfuric acid with a mass concentration of 140 g / L (the mass percentage concentration of sulfuric acid is 50 wt%), and then the surface was cleaned by washing with water, and then tested under spraying conditions. After the spraying, they were washed with deionized water, and after drying, the masses of the copper-clad substrates before and after the spraying were recorded as m1 and m2, respectively, and the micro-etching rate was calculated. During the spraying process, the temperature of the micro-etching roughening solution for high-frequency high-speed circuit boards was 30°C, and the spraying pressure was 1 kg / cm 2 , the spraying time is 1 minute; the calculation formula of the micro-etching rate is as follows.
[0068] Microetching rate = (m1-m2) / (S×ρ)×10000;
[0069] Where m1 and m2 are the mass of the copper clad laminate before and after the micro-etching treatment with the micro-etching roughening liquid spray for high-frequency high-speed circuit boards (in g); S is the area of the copper clad laminate (S = 10 × 10 × 2 = 200 cm 2 ), ρ is the density of copper, which is 8.96 g / cm3;
[0070] 2. Roughness: The surface roughness Ra value of the copper-clad substrate treated with micro-etching roughening liquid for high-frequency and high-speed circuit boards is obtained through 3D laser microscope testing;
[0071] 3. Appearance and pits: Then take out the sample and dry it, compare whether the surface of the board is evenly matte, and observe whether there are pits in the blind hole under a microscope;
[0072] 4. Storage stability: Place different micro-etching solutions in a 35°C water bath for 90 days, and measure the persulfate content in the solution. The storage stability N (%) is calculated as follows:
[0073] N = W1 × 100% / W2, where: W1 is the initial content of persulfate in the high-efficiency and stable micro-etching treatment solution (g / L), and W2 is the content of persulfate in the high-efficiency and stable micro-etching treatment solution after being placed in a 35°C water bath for 60 days (g / L).
[0074] Table 1 Performance test
[0075]
[0076]
[0077] Analyzing the data in Table 1, we can see that:
[0078] 1) The efficient and stable micro-etching treatment liquid for micro-etching treatment prepared in Examples 1 to 3 has excellent stability while having a high etching rate. The copper surface obtained by the treatment of this application is uniformly micro-etched, bright and clean, and can effectively prevent the copper surface from oxidation for a long time. The roughness of the copper surface after micro-etching is uniform, and it is suitable for micro-etching treatment of circuit boards.
[0079] 2) The performance comparison analysis of the efficient and stable micro-etching treatment solution for micro-etching treatment prepared in combination with Example 3 and Comparative Examples 1 to Comparative Examples 3 shows that the stabilizer is composed of ethylenediaminetetraacetic acid, diethylene glycol methyl ethyl ether and modified polyacrylonitrile in a mass ratio of 5:2:2-3. The synergistic effect between them is utilized to jointly maintain the stability of the micro-etching treatment solution and the uniformity of the etching effect, thereby achieving efficient and stable micro-etching treatment.
[0080] 3) The performance comparison analysis of the efficient and stable micro-etching treatment solution for micro-etching treatment prepared in combination with Example 3 and Comparative Examples 4 to Comparative Examples 6 shows that the corrosion inhibitor is composed of 1-butyl-3-methylimidazolium tetrafluoroborate, dibenzotriazole and modified imidazoline corrosion inhibitor in a mass ratio of 3:2:5. The synergistic effect between them is utilized to jointly improve the performance of the micro-etching treatment solution, ensuring efficient and uniform etching of the copper surface, while effectively preventing oxidation and corrosion of the copper surface.
[0081] 4) The performance comparison analysis of the efficient and stable micro-etching treatment liquid for micro-etching treatment prepared in combination with Example 3 and Comparative Examples 7-8 shows that the surfactant is composed of isomeric tridecanol polyoxyethylene ether and sodium isopropylbenzene sulfonate in a mass ratio of 3:2. They improve the wettability of the copper surface by reducing the surface tension of the liquid, ensuring that other chemical components can contact the copper surface more evenly and effectively. The synergistic effect between them is utilized to enhance the overall performance of the micro-etching treatment liquid. The cleaning ability of the solution for different types of pollutants can be improved while maintaining good wettability of the copper surface, which is crucial for achieving a uniform and effective etching process. In addition, this combination can also reduce the amount of surfactant used in the solution, thereby reducing costs and reducing the impact on the environment.
[0082] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. An efficient and stable micro-etching treatment solution for micro-etching treatment, characterized in that: According to mass concentration, the following raw materials are included: 98% sulfuric acid 2.8-3.2g / L, persulfate 90-120g / L, copper ion Cu 2+ ≤24g / L, tartaric acid 3-5g / L, polyethylene glycol 10-12g / L, corrosion inhibitor 3-6g / L, stabilizer 3-5g / L, surfactant 1-2g / L, accelerator 4-6g / L, wherein the copper ion Cu 2+ Supplied by a copper ion source; The stabilizer is composed of ethylenediaminetetraacetic acid, diethylene glycol methyl ethyl ether and modified polyacrylonitrile in a mass ratio of 5:2:2-3; The preparation method of the modified polyacrylonitrile is as follows: 10 parts of polyacrylonitrile powder are subjected to low-temperature heat treatment at 240° C. for 2 hours in an air atmosphere, then cooled to room temperature, and then immersed in 50 parts of a 20wt% diethylenetriamine aqueous solution for 2-3 hours, and then washed with deionized water after immersion, and then dried at 90° C. for 6-8 hours to obtain the modified polyacrylonitrile; The corrosion inhibitor is composed of 1-butyl-3-methylimidazolium tetrafluoroborate, dibenzotriazole and modified imidazoline corrosion inhibitor in a mass ratio of 3:2:5; The preparation method of the modified imidazoline corrosion inhibitor is as follows: according to the mass fraction, 170 parts of erucic acid and 100 parts of tetraethylenepentamine are added into a reactor, the temperature is raised to 150° C. and stirred for reaction for 3-4 hours, and the temperature is further raised to 210° C. and stirred for reaction for 3-4 hours to obtain the modified imidazoline corrosion inhibitor; The surfactant is composed of isomeric tridecanol polyoxyethylene ether and sodium cumene sulfonate in a mass ratio of 3:2; The accelerator is 2-mercapto-1-methylimidazole; The persulfate is one of potassium hydrogen persulfate, sodium persulfate and potassium persulfate; The copper ion source is one of copper chloride and copper sulfate; The method for preparing a highly efficient and stable micro-etching solution for micro-etching treatment comprises: adding 2.8-3.2 g of 98% sulfuric acid, 90-120 g of persulfate, and copper ions Cu 2+ ≤24g, tartaric acid 3-5g, polyethylene glycol 10-12g, corrosion inhibitor 3-6g, stabilizer 3-5g, surfactant 1-2g, and accelerator 4-6g are added to an appropriate amount of deionized water and mixed evenly, and then the mixed solution is fixed to 1L to obtain a high-efficiency and stable micro-etching treatment solution for micro-etching treatment.
Citation Information
Patent Citations
Micro-etching cleaning agent for copper surface of circuit board and preparation method of micro-etching cleaning agent
CN117210814A
Micro-etching coarsening composition, micro-etching coarsening liquid, application of micro-etching coarsening liquid, graphene-copper-based composite material and preparation method of graphene-copper-based composite material
CN117286497A
PCB copper-titanium-silver alloy ceramic plate micro-etching liquid and preparation method thereof
CN118127513A